Kisah Hidup Penderita Kanker Leher Rahim yang Mengalami Kekambuhan - Feni Elda Fitri (Jurnal Kesehatan Panca Bhakti Lampung, 2019)
Cervical cancer is a frightening disease threat to women because have risk of recurrence. This study used a qualitative approach to the narrative method about the life history, data collection was done by in-depth interviews in two participants, analysis by retelling the story of the participants in the form of theme. The purpose of research is determine the chronological experience of women who experienced recurrence of cervical cancer, which is part of the history of his life. The results of this study found several themes related chronology of women who experienced a recurrence of cervical cancer is the fulfillment of a sense of security after the treatment was complete, marks the return of the early symptoms and signs of advanced symptoms, option to go back or no to the previous health care, denial of the condition of recurrence, reducing the relationship with the community and kin, increased support when experiencing a recurrence, receiving of reccurrence condition. Hence the importance of understanding health professionals, especially nurses to know the life history of cervical cancer patients with a recurrence that can provide support and appropriate action on any recurrence period which passed in improving the quality of life.